Characteristics of Road Traffic Accident Cases Reported in a Tertiary Military Hospital (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction: Road traffic accidents (RTA) are the eighth leading cause of death globally, and the leading cause of death in Bangladesh. The road safety situation in Bangladesh has been deteriorating with increasing number of road accident deaths, largely as direct consequences of rapid growth in population, motorization, urbanization and lack of investment in road safety.Objectives: To describe the injury characteristics of road traffic accidents cases that reported at Combined Military Hospital (CMH), Dhaka.Materials and Methods: This descriptive cross-sectional hospital based study was conducted on all the RTA cases reported to medical inspection room CMH, Dhaka from 01 March to 30 June 2010. A total of 126 RTA victims irrespective of age and sex were included, data were collected by face to face interview using a pre-tested questionnaire.Results: A total of 126 road traffic accident victims both sexes were studied. The majority of the study subjects were men 103 (81.7%) and most of them were in 31-40 years group (27%), Muslims (98.41%) were the majority. In our study regarding educational qualification of RTA victims most of them were SSC qualified (44’4%) and primary level (15.1%). Military services holder (45.2%) was the majority of road traffic crash victims. Bus/Minibus (32.5%) was responsible for the majority of road traffic crashes and motor vehicle passengers (42.9%) were main victims. Laceration & cut injury were (38.1%) and multiple injury (18.3%) were the most common injury. Main roads (49.2%) were the commonest site of the accidents.  Regarding place of occurrence main roads 62 (49.2%) was the most common site and noon 41 (32.5%) was the most common time of occurrence of accidents.Conclusion: Road traffic crashes constitute a major public health problem in our setting and contribute significantly to unacceptably high morbidity and mortality. Urgent preventive measures targeting at reducing the occurrence of road traffic crashes is necessary to reduce the morbidity and mortality resulting from these injuries. Early recognition and prompt treatment of road traffic injuries is essential for optimal patient outcome.JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 213-217